Teachers' Work Intensification and Educational Contradictions in Aboriginal Communities. - Wotherspoon, Terry (Canadian Review of Sociology, 2008)
This paper explores the changing occupational nature of teaching in relation to initiatives to improve education for Aboriginal people. It examines the impact of multiple, potentially contradictory streams of educational reform. These include, in particular, concerns about the intensification of teachers' work, the professional reconstitution of teaching to meet the needs of knowledge-based societies, and consequences for Aboriginal learners and communities. Results from surveys of teachers working in Aboriginal communities in Saskatchewan and Manitoba highlight the emergence of a fragmented professionalism within teaching. Despite teachers' expressed commitment to reform, substantial changes are required if teachers' professional interests and school system practice are to become fully aligned to produce the kinds of educational success desired by Aboriginal communities. The absence of strong integrative mechanisms to link teachers' professional needs, Aboriginal community interests, and clear system commitments to education equity for Aboriginal people contributes to uneven and potentially harmful educational consequences for students who are most in need of support. Reprinted by permission of the publisher.